2005
DOI: 10.1158/0008-5472.can-04-4254
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide–Induced Apoptosis in Lymphoblastoid and Fibroblast Cells Dependent on the Phosphorylation and Activation of p53

Abstract: When nitric oxide (NO) is produced at micromolar concentrations, as during inflammation, exposure to surrounding cells is potentially cytotoxic. The NO-dependent signaling pathways that initiate cell death are thought to involve the tumor suppressor protein p53, but the degree to which this factor contributes to NO-induced cell death is less clear. Various reports either confirm or negate a role for p53 depending on the cell type and NO donor used. In this study, we have used several pairs of cell lines whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…Thus, the effect of caffeine on T cells may not be specific to inhibition of Atm. There has also been some controversy as to the effect of caffeine on Atm inhibition in cells (31), although several studies support the use of caffeine as an inhibitor of Atm in vivo (32)(33)(34)(35)(36)(37)(38)(39). In addition, caffeine is metabolized through the xanthine oxidase pathway in vivo, which stimulates ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effect of caffeine on T cells may not be specific to inhibition of Atm. There has also been some controversy as to the effect of caffeine on Atm inhibition in cells (31), although several studies support the use of caffeine as an inhibitor of Atm in vivo (32)(33)(34)(35)(36)(37)(38)(39). In addition, caffeine is metabolized through the xanthine oxidase pathway in vivo, which stimulates ROS production.…”
Section: Discussionmentioning
confidence: 99%
“…Although nitric oxide is a known activator of p53 (30,31), we recently observed that the repair of nitric oxide-damaged DNA in ␤-cells occurs by a p53-independent but GADD45␣-dependent process (32). A number of studies have shown that GADD45␣ expression is regulated by p53 (33).…”
mentioning
confidence: 99%
“…When acting upon the cell cycle machinery, NO affects multiple pathways and can contribute to cell cycle arrest through several independent mechanisms (5, 8-10, 19, 20, 22). Several major regulators of the cell cycle and stress response, e.g., cyclin-dependent kinase 2 (cdk2), cdk inhibitor p21/WAF, cyclin D1, PCNA, ribonucleotide reductase, mdm2, p53, and ataxia telangectasia mutated kinase (ATM) are involved in the cellular response to NO (2,14,18,24,25). Given the extent of NO involvement in cell physiology, it is likely that specific additional components mediate the response to NO in particular contexts.…”
mentioning
confidence: 99%